EDUCATIONAL PARADIGM: STRATEGY TO IMPROVE THE QUALITY OF LEARNING BY IMPLEMENTING LESSON STUDY - Amstrong Harefa; Ibnu Mustopo Jati; Nurul Saila (Adisam Publisher, 2024)
Learning as a part of education is the spearhead of determining whether or not educational goals are achieved, so that the quality of learning is intimately associated with the caliber of education. Lesson study implementation is one attempt to raise the standard of education in the modern world. Lesson Study is a coaching endeavor aimed at enhancing the learning process that is carried out by a group of teachers in a collaborative and ongoing manner when it comes to organizing, carrying out, monitoring, and reporting learning outcomes. An educational paradigm that includes strategies to raise the standard of instruction by using the application of lesson study is a very relevant and effective approach. Lesson Study is a cooperative approach where educators plan, monitor, and reflect on their learning together. The learning community is one of the cornerstones of lesson study. The research method used in this article is a literature review. The quality of learning, autonomous learning during lesson study, and methods for putting lesson study into practice to raise learning quality are all included in this research.